Los procesos de globalización : reflexiones sobre su concepción y efectos sobre la evolución del sistema mundial - Moneta, Carlos J. (Estudios Internacionales, 1994)
Based on the different dimensions of the globalization process and its impact on the future, this work outlines possible evolution scenarios that allow an increasing capacity for forecasting. First, an attempt is made to clarify the concept of globalization, stating that the current paradigm of international relations has changed, with two types of actors and their respective systems coexisting: the state-centric and the multicentric. Later on, the elements of the various current globalization processes are briefly examined, and it is established that this reality requires new approaches and negotiation capacity on the part of the States. Finally, regarding the different interpretations of globalization processes, reference is made to the critical vision that indicates its limitations and the tendency towards a fragmentation of the world system. Finally, it is concluded that Latin America must analyze all the options and elaborate its own long-term project.